2017
DOI: 10.15376/biores.12.2.3396-3412
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Evaluation and XRD/TG Investigation on the Properties of Wooden Dowel Welding

Abstract: Mechanical properties related to wooden dowel welding were studied using five different moisture content (MC) values. Birch wooden dowels and Chinese larch substrates were used in this study. A 2% MC for the wooden dowels and a 12% MC for the substrates resulted in the highest pullout resistance. A fitting analysis showed that there was a linear relationship between the pullout resistance and the different values of MC. The errors between the calculated values and the test values were less than 10%. The pullou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
3
8
0
Order By: Relevance
“…As the temperature of the welding interface reached about 250 °C during the welding process, the cellulose underwent a faster pyrolysis reaction under the catalysis of CuCl 2 . Finally, the relative crystallinity of the interface material in the pretreated group was lower than that of the untreated group, which was consistent with the previous X-ray diffraction (XRD) analysis [16,17]. The DTG curve showed that with the extension of welded time, the amount of cellulose pyrolysis was greater during the welding process, which was also one of the reasons for the decrease in pullout resistance.…”
Section: Tg Analysessupporting
confidence: 88%
“…As the temperature of the welding interface reached about 250 °C during the welding process, the cellulose underwent a faster pyrolysis reaction under the catalysis of CuCl 2 . Finally, the relative crystallinity of the interface material in the pretreated group was lower than that of the untreated group, which was consistent with the previous X-ray diffraction (XRD) analysis [16,17]. The DTG curve showed that with the extension of welded time, the amount of cellulose pyrolysis was greater during the welding process, which was also one of the reasons for the decrease in pullout resistance.…”
Section: Tg Analysessupporting
confidence: 88%
“…The XRD patterns of the reference and welded wood samples are illustrated in Figure 9. The X-ray diffractograms are similar to those obtained by Zhu et al (2017b) and by Zor et al (2021), when welding B. pendula, L. Gmelinii, Abies bornmulleriana, Quercus robur and Castanea sativa from northern hemisphere. These patterns refer to cellulose Iβ (JINROO01-CSD), whose main peaks are 14,9 º, 16,6 º, 22,9 º and 34,4 º (2θ) (Groom et al 2016).…”
Section: Xrdsupporting
confidence: 74%
“…For the RFW parameters adopted, the wood fibers intertwined at the interface and formed a microstructure responsible for joining the dowel and the substrate, providing mechanical strength to the joint (Zhu et al 2017b) (Figure 7d, Figure 7e, Figure 7f). Hongda et al (2022) reported a similar behavior when welding Phyllostachys edulis (680 kg/m 3 ) bamboo dowels in European spruce (700 kg/m 3 ) substrates, with feed rates of 200 mm/min, 600 mm/min and 800 mm/min.…”
Section: Microstructural Analysismentioning
confidence: 99%
“…Wood dowels immersed in CuCl2 and welded for 3 s showed a high pull-out resistance and data reliability (Zhu et al 2017a(Zhu et al , 2018(Zhu et al , 2019. In addition, the highest pull-out resistance was achieved when the moisture contents of the wooden dowels and the substrate were 2% and 12%, respectively (Zhu et al 2017b).…”
Section: Optimisation Of Wood Weldingmentioning
confidence: 94%